SUBJECTIVE WELL-BEING PADA REMAJA DARI KELUARGA BROKEN HOME - Yuli Astuti; Nisa Rachmah Nuw Anganthi (Universitas Muhammadiyah Surakarta, 2016)
This research aims to describe the factors influencing teenagers’ subjective wellbeing and the subjective well-being condition in broken home teenagers. This is a quantitative research with a phenomenology approach. The subjects are three junior high school students in the district of Wonogiri who has the following characteristics: (1) teenagers from broken home families and (2) 12 – 16 years old of ages. The data gathering methods include interview and observations. The data analyses procedurescovers open coding, axical coding and selective coding. The results show that the factors influencing subjective well-being in teenagers includes social support, parental guidance, gender, finance, and coping strategy. The subjective well-beingin Vn ad DN are better than informan An. It occurs in life satisfaction asspect and apparently showed in some facts, such as graduating elementary school with good grades and getting a bicycle as a present. Some acts that can bring positive effect covers vacation with the family, helping the family, sports championships and getting good grades at school. The acts that can bring negative effect include feeling guilty, do not have pocket money, negative thoughts toward father and the neighbours, thinking off father, getting bad grades, family loss, mother who always gets angry,and jealousy towards friends.